The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/15567249.2020.1773579
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the determining factors of fuel poverty among students living in the private-rented sector in Europe and its impact on their well-being

Abstract: Existing research suggests that students are an under-reported and undersupported group of the population that frequently lives in fuel poverty. Furthermore, studies show that students do not realize that they live in fuel poor conditions and are rarely recognized as a group vulnerable to fuel poverty. The aim of the research presented in this paper is to understand, evaluate and consequently reveal the experiences of students living in the private-rentedd sector, quantify their possible exposure to fuel pover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 44 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…Previous studies that have focused on young people's energy consumption have looked at energy and at information and communication technologies among youths (Christensen et al 2014;Christensen and Rommes 2019); students living in fuel poverty (Kousis et al 2020;Morris and Genovese 2018); and energy vulnerability (Bouzarovski et al 2013). Scholars have found that students and young people are rarely recognized as a group vulnerable to energy poverty, and many students and young people do not recognize that they live in energy-poor conditions (Bouzarovski et al 2013;Kousis et al 2020). Energy poverty is broadly understood as the inability of households to maintain adequate levels of energy services at an affordable cost, and is caused by the interplay of low incomes, high energy need, and high energy prices (Doukas and Marinakis 2020).…”
Section: Student Life and Energy Usementioning
confidence: 99%
“…Previous studies that have focused on young people's energy consumption have looked at energy and at information and communication technologies among youths (Christensen et al 2014;Christensen and Rommes 2019); students living in fuel poverty (Kousis et al 2020;Morris and Genovese 2018); and energy vulnerability (Bouzarovski et al 2013). Scholars have found that students and young people are rarely recognized as a group vulnerable to energy poverty, and many students and young people do not recognize that they live in energy-poor conditions (Bouzarovski et al 2013;Kousis et al 2020). Energy poverty is broadly understood as the inability of households to maintain adequate levels of energy services at an affordable cost, and is caused by the interplay of low incomes, high energy need, and high energy prices (Doukas and Marinakis 2020).…”
Section: Student Life and Energy Usementioning
confidence: 99%
“…Studies exploring energy poverty among tertiary student population groups in England [19][20][21], Europe [22,23], and Japan [24] have confirmed that tertiary students are at greater risk compared to the general population. Poor housing conditions, particularly in the private rental sector, contribute to adverse mental and health outcomes among tertiary students [19,22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies exploring energy poverty among tertiary student population groups in England [19][20][21], Europe [22,23], and Japan [24] have confirmed that tertiary students are at greater risk compared to the general population. Poor housing conditions, particularly in the private rental sector, contribute to adverse mental and health outcomes among tertiary students [19,22]. As with other studies of private rental sector landlords [16,25,26], a qualitative study of landlords in seven EU countries found that landlords with properties predominantly leased by students are unlikely to make energy efficiency improvements to their rental housing without financial incentives and regulatory measures.…”
Section: Introductionmentioning
confidence: 99%
“…UHI is a significant human-induced environmental change that poses threats to human life. For instance, increased morbidity and mortality 12 , indoor/outdoor discomfort 13 , air pollution 14 , 15 , increased energy consumption 16 and greenhouse gas emissions 17 , 18 , impaired air and water quality 19 and intensification of energy poverty on vulnerable social groups during the hot months of the year 20 , 21 are just some of UHI consequences that usually are interconnected. Also, UHI is associated with global warming and moreover has been found to synergistically act with heatwaves and amplify their impacts 22 24 .…”
Section: Introductionmentioning
confidence: 99%